THE IMPLEMENTATION OF THE PROFIL PELAJAR PANCASILA AT SD NEGERI SIDOREJO 01 WARUNGASEM - Maghfiroh, Ana Tri Dewi; Muslim, Rachmat Imam; Aditama, Madya Giri (Prosiding University Research Colloquium, 2023)
Era Society 5.0, the national education system carries out reforms in a planned, targeted and sustainable manner to ensure equity in education, improve quality, and increase the relevance and efficiency of education management. So, the Ministry of Education and Culture established an independent curriculum with the development of the Profil Pelajar Pancasila character. The purpose of this study was to analyze the implementation of the Profil Pelajar Pancasila and to describe the differences in the application in each dimension of the Profil Pelajar Pancasila at SD Negeri Sidorejo 01 Warungasem. This research method uses a qualitative approach with a type of phenomenology, and data collection techniques through observation techniques, in-depth interviews, and documentation studies. In addition, this study used Miles & Huberman’s data analysis procedures: data reduction, data display, drawing conclusions and verification and deepening using source triangulation, method triangulation, and time triangulation. The results showed that the implementation of the Profil Pelajar Pancasila at Sidorejo 01 Warungasem Public Elementary School, namely through the school culture of entrepreneurship, intra-curricular learning with the habituation of religious morals, personal morals, morals towards humans, morals towards nature, and national morals. and scout and marching band extracurricular activities. From the implementation of the 6 dimensions of the Profil Pelajar Pancasila the most dominant are faith, piety to God Almighty, and have noble character. Based on these data it can be concluded that the implementation of the Profil Pelajar Pancasila at SD Negeri Sidorejo 01 Warungasem through the school culture of entrepreneurship, intracurricular learning and extracurricular activities of scouts and the Marching Band.